دراسة مرجعية عن تأثير دورات الجفاف والرطوبه على تلف الخرسانة المعرضة لكبريتات الصوديوم (Comprehensive Journal of Science, 2025)
The problem of concrete damage due to interaction with sodium sulfate is one of the important issues in structural engineering, especially in areas that are exposed to severe climate fluctuations. The effect of drought and humidity cycles is one of the main factors that contribute to increasing the effect of this reaction, as these cycles cause cracks inside the concrete as a result. Due to continuous changes in size due to expansion and contraction resulting from the absorption and evaporation of water, Where sodium sulfate reacts with calcium hydroxide in concrete, forming sulfate hydrate, which leads to an increase in the volume of the produced material and causes the concrete to expand and crack. This reaction becomes more severe in conditions of dry and wet cycles, as these cycles facilitate the absorption of water again into the concrete, which It enhances the reaction with sodium sulphate and increases the deterioration of concrete.This reference study aims to study the effect of environmental factors such as changes between dryness and humidity on the durability of concrete, in addition to the effect of concrete’s interaction with sodium sulfate, as it can interact with concrete components, leading to its deterioration or corrosion. The importance of this is to understand how sodium sulfate affects the concrete structure, especially in environments containing high concentrations of sodium sulfate.The study concluded that the use of materials and techniques that enhance durability can help reduce the effects of the sodium sulfate reaction and ensure the sustainability of concrete in these environments, such as partially replacing Portland cement with fly ash, where the appropriate amount of fly ash can effectively improve the internal structure of concrete to reduce corrosion damage and reduce the rate of Mixing water can improve the resistance of concrete to sodium sulphate attack Increasing the period of the dry and wet cycle gradually leads to an increase in the depth of the effect of sulfate attack within the concrete, and therefore the effect of dry and wet cycles must be taken into account when designing concrete structures in environments exposed to climate fluctuations.
Keywords: sodium sulphate, Dry-wet cycles, Corrosion, sulfate attack